ОСНОВНЫЕ ПРИНЦИПЫ И МЕТОДЫ ПЕРВИЧНОЙ ПРОФИЛАКТИ КИИШЕМИЧЕСКОЙ БОЛЕЗНИ СЕРДЦА У НАСЕЛЕНИЯ, ПРОЖИВАЮЩЕГОВ УСЛОВИЯХ ЭКОЛОГИЧЕСКОГО НЕБЛАГОПОЛУЧИЯ («Наука и здравоохранение», 2026)
In the paper we have presented the basis and description for the method of detection, main principles and methods forthe primary prophylactics of ischemic heart disease in the population living in unfavorable ecological conditions. Its application assists to conduct the early diagnostic for cardiovascular diseases and their effective prophylactics.